Temperature and productivity in soccer - Vojtěch Mišák (Charles University in Prague, Institute of Economic Studies (IES), 2025)
This paper examines the impact of temperature on soccer team productivity using match-level data from ten countries across three continents. The results show that temperature affects multiple performance metrics, often in non-linear ways. Specifically, attacking efficiency is enhanced in warmer conditions, leading to increased goal productivity and improved shot conversion rates. Conversely, defensive performance appears to weaken in warmer conditions, with a decrease in defensive pressure and passing accuracy. Player aggression follows an inverted U-shaped pattern in relation to temperature. The effects of temperature vary across different leagues and climate regions. The relationship between temperature and outcome measures tends to be stronger in lower leagues, while the Champions League is the least influenced overall. Teams from colder regions experience a larger decline in passing volume when playing in high temperatures, with the effect being particularly pronounced in Brazil.
Keywords: K14; K42; K49; 330; Football; Soccer; Temperature; Weather; Productivity